SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN BUKU BERBASIS WEB PADA DINAS PERPUSTAKAAN DAN KEARSIPAN - Rabiatul Adwiya (STMIK KAPUTAMA, 2021)
Web-Based Book Loaning and Retrieval Information Systems at Bengkayang Library and Archives Service is one of the centers of community information and archival arrangements established under Bengkayang District Regulation No. 4 of 2006.The data processing processes carried out at the Bengkayang Library and Archives Service are generally still manual, such as recording on member data, book data, borrowing data, and book returns.In order to help the library to be able to improve services in the loan and repayment process to be faster and more accurate. The method of developing the Book Loan and Returns System is made using the waterfall method as a system developer tool, while for collecting data the writer uses observation, interviews and library studies conducted at the Bengkayang Library and Archive Service.The design of the system created aims to minimize the level of errors found in the library, using the web created as a program, Mysql and PHPMyadmin as a database, Wamp Server as a database liaison. With this computerized system to achieve an activity that can support the activities of Lending and Returning Books to be more effective and efficient compared to the first system.